PACTO PRIVADO FEUDAL Y ESTRUCTURA PUBLICA EN LA ORGANIZACION DEL PODER POLITICO EN LA ALTA EDAD MEDIA (Res Publica. Revista de Historia de las Ideas Políticas, 2023)
The author upholds the idea of the feudalisation of the kingdom of León being before its time, particularly if we compare it with the feudalisation of the county of Barcelona. But this feudal reality does not prevent us from recognising at the same time the continuation and development of another reality: the concept of royal power which the Visigothic legislation had inherited from Rome. This concept survived in a latent state through the 10th century and began to be revived at the beginning of the 11th century with the decreta of 1017 issued by Alfonso V.